UTHM Residential Booking System - Zamri, Mukhlisatul Waasiqah; Mohd Zaki Mohd Salikon (Applied Information Technology And Computer Science, 2023)
The hostel booking system is an aspect that needs to be emphasized by a university. Parit Raja Campus Residential College is one of the residential colleges that used a booking system to book hostels for all its students. Thus, this web-based system was created to facilitate students to know if the college and room that they want to use are available or not at that time. This system is designed into two sections which are the administrator and student section and four main modules which are the login module, student module, room allotment module, and settings module. This project is implemented using the prototype model and Bracket development software, MySQL as the database and PHP as the scripting language. The hostel booking system will be the ideal way to handle resident management issues because it will allow for simple online applications. Therefore, a hostel that operates without any problems or errors aids the educational institution in strengthening its own brand.